2012
DOI: 10.4314/ajpsy.v15i2.13
|View full text |Cite
|
Sign up to set email alerts
|

Burden and psychological effects : caregiver experiences in a psychiatric outpatient unit in Lagos, Nigeria

Abstract: Objective: Worldwide, research into experiences of care givers are gradually increasing and their central role in community care is being acknowledged. Caregivers experience a multidimensional range of problems, often associated with their caregiving role. It becomes important to identify these areas of burden and provide necessary support. The study sought to determine the prevalence of psychological distress and experience of burden of care among the caregivers of mentally ill patients. Method: A cross secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
21
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 34 publications
13
21
1
2
Order By: Relevance
“…Due to the 'burden of care' in their care giving processes, caregivers experienced anxiety, fear, sadness, sleeplessness, loss of appetite, loss of libido and depression. Similar observations were made in other studies done on family caregivers (American Psychiatric Association 2014, Oshodi et al 2012). Depression, anxiety, irascibility, and cognitive disruptions were outcomes of the caregiver stress process (Pearlin et al 1990).…”
Section: Discussionsupporting
confidence: 90%
“…Due to the 'burden of care' in their care giving processes, caregivers experienced anxiety, fear, sadness, sleeplessness, loss of appetite, loss of libido and depression. Similar observations were made in other studies done on family caregivers (American Psychiatric Association 2014, Oshodi et al 2012). Depression, anxiety, irascibility, and cognitive disruptions were outcomes of the caregiver stress process (Pearlin et al 1990).…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, the results of regression analysis demonstrated that caregiver burden was able to predict 0.05 of physical quality of life and mental quality of life (dimensions of quality of life) and 0.07 of physical suffering (dimension of perception of suffering), 0.05 of mental suffering (dimension of perception of suffering), and 0.05 of existential suffering (another dimension of perception of suffering). These results are in line with the results obtained from some previously conducted studies determining that caregiver burden was significantly and positively related to physical and mental dimensions of quality of life and it was significantly and inversely correlated with physical, mental, and existential dimensions of perception of suffering (14)(15)(16)(17)(18)(20)(21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 91%
“…Schulz et al, in their study, found that caregivers' perception of suffering was correlated with patients' pain and suffering (21). The findings obtained from a study carried out by Oshodi et al indicated that patients' caregivers suffered from high levels of psychological stress (22).…”
Section: Introductionmentioning
confidence: 95%
“…Specifically, studies have identified a bi-directional relationship between caregiving burden and psychological distress among patients with various chronic medical illnesses [13,15,16]. Unfortunately, while caregiver burden has been extensively examined in relation to many chronic illnesses [15][16][17][18][19], there appears to be none among caregivers of children with OAT. Similar scenarios have been reported in the developed world [15] as caregivers have often been referred to as the hidden patients [16].…”
mentioning
confidence: 99%